A study of survival strategies for improving acclimatization of lowlanders at high-altitude. Issue 4 (April 2023) - Sharma, Poornima; Mohanty, Swaraj; Ahmad, Yasmin
Abstract: Human Acclimatization and therapeutic approaches are the core components for conquering the physiological variations at high altitude (≥2500 m) exposure. The declined atmospheric pressure and reduced partial pressure of oxygen at high altitudes tend to decrease the temperature by several folds. Hypobaric hypoxia is a major threat to humanity at high altitudes, and its potential effects include altitude mountain sickness. On severity, it may lead to the development of conditions like high-altitude cerebral edema (HACE) or high-altitude pulmonary edema (HAPE) and cause unexpected physiological changes in the healthy population of travelers, athletes, soldiers, and low landers while sojourning at high altitude. Previous investigations have been done on long-drawn-out acclimatization strategies such as the staging method to prevent the damage caused by high-altitude hypobaric Hypoxia. Inherent Limitations of this strategy hamper the daily lifestyle and time consuming for people. It is not suitable for the rapid mobilization of people at high altitudes. There is a need to recalibrate acclimatization strategies for improving health protection and adapting to the environmental variations at high altitudes. This narrative review details the geographical changes and physiological changes at high altitudes and presents a framework of acclimatization, pre-acclimatization, and pharmacological aspects of high-altitude survival to enhance the government efficacy and capacity for the strategic planning of acclimatization, use of therapeutics, and safe de-induction from high altitude for minimizing the life loss. It's simply too ambitious for the importance of the present review to reduce life loss, and it can be proved as the most essential aspect of the preparatory phase of high-altitude acclimatization in plateau regions without hampering the daily lifestyle. The application of pre-acclimatization techniques can be a boon for people serving at high altitudes, and it can be a short bridge for the rapid translocation of people at high altitudes by minimizing the acclimatization time.